Shaping Ecological Norms for the Protection of Water Resources – Comment on the Judgment of the International Court of Justice in the Chile v. Bolivia Case (Dispute over the Status and Use of the Waters of the Silala, Judgment of 1 December 2022) - Kowalska , Samanta (Polish Review of International and European Law, 2024)
On 1 December 2022, the International Court of Justice (ICJ) issued a judgment in the dispute over the Status and Use of the Waters of the Silala, Chile v. Bolivia (Judgment). The Judgment aroused public interest, but did not bring the expected resolutions in norms of public international law. The status and management of Silala waters is currently primarily influenced by political, economic and capital factors. Economic factors weaken the protection of water resources, contributing to the deepening of the social and ecological crisis. In the face of global warming and climate change, questions about how to deal with sensitive natural resources under international law are more relevant than ever before. Therefore, the need to take into account the holistic context related to the importance of water for human functioning and the entire ecosystem will be emphasized in the course of the article. The author will present arguments indicating that the Silala ruling may provide guidance for the development of international environmental law and the formation of an ecological reference point for the newly emerging field of international water law.